The Gender Gap on Reading Habit of ELF Students - Aprilianti, Berliana Dyah Ayu; Puspitasari, Evi (Proceeding Universitas Muhammadiyah Yogyakarta Graduate Conference, 2020)
Literacy issues become one of the problems in an educational field. As stated in the Sustainable Development Goals number four about quality education, this research has raised. Nowadays, in this modern era, children are influenced by gaming or playing social media rather than reading real books or virtual books. Meanwhile, the education field has technologized, it is easier to search something or just to read several pages each day. Based on UNESCO (2014), Indonesian children only read 27 pages each year. The low number of reading habits in Indonesia pushes the researcher to explore the gender gap on reading habits, especially the reading habit of EFL students in English Language Education Department in one of private university in Yogyakarta. The researcher spread the questionnaire to the English Language Education Department’s active students in one of private university in Yogyakarta. The result showed that there is a gap between male and female students on reading habits on their books choice and how the way their habit on reading. Therefore, after getting the result, the researcher hopes that the result of this study could inform the English Department of choosing an appropriate book or activities to the students, or more push the students to read a lot such as giving a reading assignment and it is sustainable.